The role mission does (or does not) play in Faith and Order’s The Church - Wilson, Sarah Hinlicky 197X- (Vox scripturae, 2014)
Mission is a popular byword in ecumenical circles today, but it remains oddly lacking in content. An examination of the recent paper "The Church" by the Faith and Order Commission reveals how despite lip service to the concept of mission, its ecclesiology is dominated by an institutionalized, inward-looking, clergy-focused approach, which simply reinforces all of the most intractable divisions between churches. Notable too is the absence of any discussion of sin or interpretation of church history. It is suggested that deeper engagement with missional practice and theology could break up the current deadlock in ecumenical ecclesiology.